2015
DOI: 10.1007/s10856-015-5415-5
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the influence of Na+ and Sr2+ on the structure and solubility of SiO2–TiO2–CaO–Na2O/SrO bioactive glass

Abstract: This study was conducted to determine the influence that network modifiers, sodium (Na+) and strontium (Sr2+), have on the solubility of a SiO2-TiO2-CaO-Na2O/SrO bioactive glass. Glass characterization determined each composition had a similar structure, i.e. bridging to non-bridging oxygen ratio determined by X-ray photoelectron spectroscopy. Magic angle spinning nuclear magnetic resonance (MAS-NMR) confirmed structural similarities as each glass presented spectral shifts between -84 and -85 ppm. Differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 19 publications
5
12
0
Order By: Relevance
“…The normalized EDS spectra of the synthesized glasses after incubation in SBF revealed that the calcium and phosphorus on the surface of the incubated glass powders increase with immersion time (Figure ). Similar trends have been reported for incubated bioactive glasses . The observed increase in the intensity of the Ca, P, and Zn peaks in the EDS spectra can be seen as an indication of formation of CaP layer, where Ca seems to be partially replaced by Zn; this partial replacement of Ca with Zn has been previously reported for other bioactive glasses with Zn in their composition .…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…The normalized EDS spectra of the synthesized glasses after incubation in SBF revealed that the calcium and phosphorus on the surface of the incubated glass powders increase with immersion time (Figure ). Similar trends have been reported for incubated bioactive glasses . The observed increase in the intensity of the Ca, P, and Zn peaks in the EDS spectra can be seen as an indication of formation of CaP layer, where Ca seems to be partially replaced by Zn; this partial replacement of Ca with Zn has been previously reported for other bioactive glasses with Zn in their composition .…”
Section: Resultssupporting
confidence: 87%
“…SEM images of the powders after 24 h immersion in SBF showed precipitations on the surface for all five compositions (Figure ). The morphology of the observed precipitations is comparable to CaP and HA precipitations on bioactive glasses reported in the literature . The normalized EDS spectra of the synthesized glasses after incubation in SBF revealed that the calcium and phosphorus on the surface of the incubated glass powders increase with immersion time (Figure ).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Furthermore, SrO and MgO amounts were kept unchanged from the Bio_MS composition because such oxides have been shown to further contribute to decrease the glass transition temperature T g and increase the crystallization temperature T c [ 19 , 20 , 21 , 22 ]. Nonetheless, the incorporation of SrO and MgO not only aims to improve thermal properties but it also aims to enhance the biological performance; it has been reported that Sr and Mg ions improve effectiveness for bone regeneration [ 23 , 24 , 25 , 26 ] and cell proliferation [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%